"This Is a Quiet Library, Except When It's Not:" On the Lack of Neurodiversity Awareness in Librarianship. (3rd April 2019) - Tumlin, Zachary
ABSTRACT: While much has been written about diversity, disability, and specific neurominorities in information studies and music, the subject of neurodiversity as a whole has remained relatively untouched since it first appeared 20 years ago. This paper briefly reviews what few pieces do exist, then begins to fill that gap by laying a foundation for future scholarship. The history and vocabulary of neurodiversity are outlined, concepts from Disability Studies are introduced (like identity-first language and models of disability), and neurodivergent voices (besides the author's own) are promoted. The author would like to state that as a neurodivergent person, his writing style may not meet traditional (i.e., neurotypical) standards, especially those in academia, which can be a particularly exclusionary and ableist environment. While he does not wish to be a "bad writer, " he also does not believe in altering his authentic, disabled voice simply to make it more palatable for the able-bodied and minded. He would like to thank the editors of this journal for their inclusivity and encourage readers to always seek out and privilege the voices of self-advocates over advocates.